Speaking in Tongues: What Parents Really Think About Tongue-Tie Surgery for Their Infants. (March 2020) - Ray, Shagnik; Hairston, Tai Kyung; Giorgi, Mark; Links, Anne R.; Boss, Emily F.; Walsh, Jonathan
We evaluate maternal perspectives of frenotomy for ankyloglossia in newborns. We searched highly frequented forums likebabycenter.com for comments related to frenotomy posted from 2012 to 2017. We applied modified grounded theory, reviewed posts for thematic synthesis, and calculated frequencies for each theme. High decisional conflict, low discussion of surgical complications, and an overall moderate positive experience were noted. Mothers posted about breastfeeding issues (n = 227, 74.7%) and overall experience (n = 229, 75.3%). Posts related to breastfeeding include discomfort ("I can no longer physically take the pain"; n = 93, 30.6%). Parents posted frequently about a satisfactory outcome ("It was so worth it to improve our nursing relationship"; n = 133, 43.8%), but dissatisfactory outcome ("I'm still having problems latching and am pumping. It's brutal"; n = 31) was present in 10.2%. These results aid in understanding parental thoughts of frenotomy. Physicians can use these self-reported maternal perspectives on frenotomy to guide counseling and improve shared decision making for parents.